2016
DOI: 10.14405/kjvr.2016.56.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma N-terminal pro-brain natriuretic peptide and troponin I concentrations in dogs with congenital ventricular outflow tract stenosis

Abstract: This study evaluated the levels of cardiac biomarkers in dogs with either pulmonic stenosis or aortic stenosis and the correlation between biomarkers and the severity of stenosis assessed by the echocardiography. To achieve this study goal, 38 dogs (10 healthy control dogs, 15 dogs with pulmonic stenosis and 13 dogs with aortic stenosis) were examined. The jet velocity and pressure gradient in this study population were measured by echocardiographic estimation, after which the study group was subdivided by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Using the same methodology, Kim, Suh, and Hyun (2020) measured the urinary blood loss in nine patients who had severe hematuria and an infection with S. haematobium. The results showed that the daily mean iron loss ranged from 0.6 to 37.3 mg and that the blood loss varied from 2.6 to 126 mI/day [16,22]. They pointed out that while a S. haematobium infection can cause severe urinary blood loss, this loss typically occurs suddenly and is not continuous like it would be with a hookworm infection [16,22].…”
Section: S Haematobiummentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same methodology, Kim, Suh, and Hyun (2020) measured the urinary blood loss in nine patients who had severe hematuria and an infection with S. haematobium. The results showed that the daily mean iron loss ranged from 0.6 to 37.3 mg and that the blood loss varied from 2.6 to 126 mI/day [16,22]. They pointed out that while a S. haematobium infection can cause severe urinary blood loss, this loss typically occurs suddenly and is not continuous like it would be with a hookworm infection [16,22].…”
Section: S Haematobiummentioning
confidence: 99%
“…The results showed that the daily mean iron loss ranged from 0.6 to 37.3 mg and that the blood loss varied from 2.6 to 126 mI/day [16,22]. They pointed out that while a S. haematobium infection can cause severe urinary blood loss, this loss typically occurs suddenly and is not continuous like it would be with a hookworm infection [16,22].…”
Section: S Haematobiummentioning
confidence: 99%